PENINGKATAN PENGETAHUAN SEBAGAI UPAYA DETEKSI DINI ANEMIA MELALUI EDUKASI KESEHATAN PADA LANSIA - Tia (Jurnal SADEWA, 2026)
Anemia in the community, especially among the elderly and women, remains a significant health problem and is often undetected due to low awareness and limited health screening. This community service activity aimed to improve knowledge and promote early detection of anemia through health education and hemoglobin (Hb) examination. The method included interactive educational sessions on anemia, covering its definition, causes, symptoms, prevention, and management, followed by Hb screening using a portable device and brief counseling. A total of 35 participants were involved in this activity. The results showed an increase in participants’ knowledge after the education session. Hb examination revealed that 68.6% of participants had normal Hb levels, while 31.4% were identified as having low Hb levels or being at risk of anemia. Participants with low Hb received counseling and were advised to seek further medical examination. This activity demonstrated that the combination of education and Hb screening is effective in increasing awareness, improving knowledge, and detecting anemia early in the community. Therefore, similar programs are recommended to be conducted regularly to enhance public health outcomes and prevent anemia-related complications